Leading Public Transportation Drivers In Integrating Traffic Ethics Based on Nation Characters Value at Padang City - Erianjoni Erianjoni; Jamalul Ihsan (Journal of Education on Social Science (JESS), 2017)
This article discussed about the public transportation drivers traffic ethics. It was found that the drivers’ attitude was accessed by societies from its good and bad or right and wrong side. These attitudes were the reflection of drivers’ ethics. It was rarely seen that the public transportation drivers in Padang owned the ethics of Indonesian character such as religious, honest, care, responsible, discipline, and tolerant. As the result, there were some traffic phenomenon in Padang like traffic jam, accident, and violation. Therefore, it was crucial to improve the drivers’ ethic which referred to Nation Character in order to create comfortableness in road traffic. The research result in this article tried to find the solution of the previous problem.